The effect of aluminium on twinning in binary alpha-titanium. (15th January 2016) - Fitzner, Arnas; Prakash, D.G. Leo; da Fonseca, Joao Quinta; Thomas, Matthew; Zhang, Shu-Yan; Kelleher, Joe; Manuel, Pascal; Preuss, Michael
Abstract: The deformation mechanisms of binary Ti–Al model alloys (0–13.1 at.% Aluminium) have been investigated with respect to the twinning activity using in-situ loading in combination with neutron diffraction as well as detailed post mortem electron backscatter diffraction analysis. A consistent starting grain size and texture was generated for all alloys promoting tensile twinning during compression testing. Long-wavelength neutron diffraction and selected area diffraction transmission electron microscopy analysis were carried out to detect evidence of Aluminium ordering and Ti3 Al formation. It was found that raising the Aluminium content in Titanium does first slightly enhance twinning, with {10 1 ¯ 2}<10 1 ¯ 1> tensile twinning being by far the dominant type, while the critical residual intergranular strains for twin initiation decreases. This suggests that either the lowering of stacking fault energy by Aluminium or its solute solution strengthening effect are important factors. At around 7 at.% Aluminium a turning point in twinning activity was noticed and a further increase in Aluminium did result in a dramatic loss of twinning activity particularly when the material had been exposed to an additional low temperature age. The dramatic decrease of twinning activity is strongly correlated with increasing evidence of short range ordering and also early signs of Ti3 Al-formation in case of the highest Aluminium content. In addition, electron backscatter diffraction analysis revealed that the formation of Aluminium ordered zones do severely hinder growth of twin boundaries. Graphical abstract: